Nitrogen and Phosphorus Removal from Low Carbon/Nitrogen Wastewater in an Anaerobic/Oxic/Anoxic Process with Endogenous Denitrification at Different DO Concentrations - Tea Štefanac; Dijana Grgas; Irena Landeka Jurčević; Sanja Radman; Mirna Habuda-Stanić; Tibela Landeka Dragičević (Kemija u Industriji, 2025)
The effect of selected dissolved oxygen (DO) concentrations (DO ≥ 2 mg l−1 and DO ≈ 1 mg l−1) on nitrogen (N) and phosphorus (P) removal was investigated in the treatment of wastewater with a low C/N ratio using an anaerobic/oxic/anoxic (A/O/A) process with endogenous denitrification. The selected DO significantly influenced the efficiency and rate of N removal. The N loss of 43 and 71 %, due to simultaneous nitrification and denitrification in the oxic phase of the A/O/A process, were observed at ≥ 2 mg DO l−1 and ≈ 1 mg DO l−1, respectively. The NH4-N removal rate of 11.2 mg NH4-N lh−1 and the PO4-P uptake rate of 9 mg PO4-P lh−1, and NH4-N removal rate of 9.4 mg NH4-N lh−1 and PO4-P uptake rate of 9.4 mg PO4-P lh−1 at ≥ 2 mg DO l−1 and ≈ 1 mg DO l−1, were determined. P removal of 78.5 % and N removal of 76.6 % (in the A/O/A process at DO ≥ 2 mg l−1), and P removal of 77.9 % and N removal of 95.3 % (in the A/O/A process at DO ≈ 1 mg l−1) were achieved.